MOLECULAR GENETICS STUDY FUNCTIONING POLYMORPHIC GENE VARIANTS CYTOKINE NETWORK AND BIOTRANSFORMATION OF XENOBIOTICS FOR CANCER - E. V. Vorobyeva; E. M. Vasilyeva; G F. Galikeeva; V. Y. Gorbunova (Креативная хирургия и онкология)
The interrelation of polymorphic loci genes  cytokine profile with indicators spontaneous cytokine  production oxists.  Combination of  genotypes identified family interleukin  -1, and having functional significance adaptive " mutant " alleles (* E2/* II /* C) in the genes of the interleukin -1 was significantly  more frequent in cancer patients " risk" alleles of the tumor  suppressor gene TP53. It’s revealed that  the cancer patients in the combined genotype " mutant " alleles in the gene not only NQO1, but also genes of the interleukin -1 wich where studied.